Macrozoobenthos community structure as a bioindicator of water quality in the Banjaran River, Banyumas - Wahyuningsih, Eti; Rahayu, Nur Laila; Zaenuri, Musyarif (Universitas Malikussaleh, 2024)
The Banjaran River is one of the rivers in the Banyumas Regency. This research aims to produce information related to macrozoobenthic community structure as a bioindicator of water quality in the Banjaran River and to produce information related to water quality in the Banjaran River for macrozoobenthic life. The research was conducted in September 2022 - February 2023 on the Banjaran River, Banyumas. This research uses a survey method, sampling was carried out 3 times in September-November 2022. The sampling method was purposive random sampling, namely the river was divided into 3 stations based on certain criteria. The results of this research obtained 15 species and were divided into 11 families, namely Perlidae, Psychomyiidae, Thiaridae, Lumbricidae, Naididae, Gecarcinucidae, Palaemonidae, Elmidae, Hydropsychidae, Atyidae, and Chironomidae in the Banjaran River. The highest abundance of individuals was at station two, namely 3156 individuals/m2. The dominant species is Melanoides tuberculata with an abundance of 1852 individuals/m2 at station two. The dominance index values at the three stations ranged from 0.1864 to 0.2886, which is relatively low. The water quality in the Banjaran River for macrozoobenthic life is still quite good based on the results of measuring environmental parameters which consist of physical parameters, namely water temperature and current speed.Keywords: Banjaran River, Macrozoobenthos Community, Water Quality Indicators